2018
DOI: 10.1002/ejp.1326
|View full text |Cite
|
Sign up to set email alerts
|

Exposure and cognitive‐behavioural therapy for chronic back pain: An RCT on treatment processes

Abstract: Background To improve treatment outcomes, it is essential to understand the processes involved in therapeutic change. The aim of this study was to investigate the processes involved in treatment of individuals with chronic lower back pain (CLBP) and high fear‐avoidance. Graded in vivo exposure (Exposure), a specific treatment, and cognitive‐behavioural therapy (CBT), a general treatment, were compared. Methods Our study used data from a three‐arm randomized controlled trial. The sample comprised 61 CLBP patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 46 publications
2
23
0
Order By: Relevance
“…These findings are in line with studies showing that improved catastrophizing and painacceptance mediate effects on pain interference in similar cognitive-behavioral treatments focusing on exposure, values and pain-coping [26][27][28] . In addition, these results add to the increasing empirical support for the theoretical assumption that pain interference, catastrophizing, inactivity and lack of reinforcement are important factors in the development and maintenance of depression in the context of chronic pain 8,68,69 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings are in line with studies showing that improved catastrophizing and painacceptance mediate effects on pain interference in similar cognitive-behavioral treatments focusing on exposure, values and pain-coping [26][27][28] . In addition, these results add to the increasing empirical support for the theoretical assumption that pain interference, catastrophizing, inactivity and lack of reinforcement are important factors in the development and maintenance of depression in the context of chronic pain 8,68,69 .…”
Section: Discussionsupporting
confidence: 90%
“…Improvement on measures regarding pain-related dysregulation (such as: the Pain Catastrophizing Scale, PCS 26 ; the Tampa Scale of Kinesiophobia, TSK 27 ; and the Chronic Pain Acceptance Questionnaire, CPAQ 28 ) have been shown to mediate effects on pain interference and disability in both CBT treatments and physical therapy for patients with chronic pain [26][27][28] , and reductions in emotion dysregulation (including several measures of difficulties in emotion regulation, rumination, and experiential avoidance) have been shown to correlate with effects on emotional problems such as depressive symptoms in multiple psychological treatments for psychiatric disorders 14 .…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has found moderate evidence that health care professionals with a biomedical orientation or elevated fear-avoidance beliefs themselves are more likely to advise patients to limit physical activities [29], which in turn can affect patients' outcomes [42]. Consequently, there is a future need for interventions aimed at addressing clinicians' beliefs about LBP and the benefits of staying active, with a focus on building clinical skills to optimise reassurance [43]. This may enable healthcare professionals to identify and effectively address factors such as fear-avoidance, self-efficacy, catastrophising, and recovery expectations [9,10] that may importantly influence LBP recovery.…”
Section: Unanswered Questions and Future Researchmentioning
confidence: 99%
“…The principles of learning theory and the key role of avoidance are increasingly recognized within biopsychosocial disease models and have been successfully translated into extinctionbased interventions in various psychiatric and psychosomatic conditions. Inspired by their wide application in anxiety disorders (30,32,36,77), exposure therapy has been established as an integral part of multimodal interventions for disorders characterized by disturbed interoception (78), including chronic pain (38,54,79,80), disorders of the gut-brain axis, particularly irritable bowel syndrome (IBS) (48,(81)(82)(83)(84), but also for body image disturbances and eating disorders (85)(86)(87)(88), substance abuse and addiction (89)(90)(91).…”
Section: Clinical Implications Of Avoidance In Psychosomatic Medicinementioning
confidence: 99%